Antimicrobial susceptibility to b-lactams and metronidazole of microorganisms isolated from chronic and aggressive periodontitis - Gaetti-Jardim Júnior, Elerson [UNESP]; Schweitzer, Christiane Marie [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2013)
The objective of this study was to evaluate the microbial susceptibility to ß-lactams and metronidazole, and evaluate the production of ß-lactamases by microorganisms isolated from patients with chronic or aggressive periodontitis. The samples were obtained from 50 patients with periodontitis and microorganisms were isolated onto selective and nonselective culture media, identified by biochemical methods and tested for susceptibility to antimicrobial agents (amoxicillin, amoxicillin/clavulanate, cefoxitin, imipenem, metronidazole, penicillin G). The isolates were resistant to at least 1 mg/ml of any drug tested were evaluated to verify the production of ß-lactamases by the method of double layer (or biological) and chromogenic cephalosporin using nitrocefin. The results evidenced resistance to amoxicillin and penicillin G, while the susceptibility to association amoxicillin/clavulanate, imipenem and cefoxitin was widely disseminated among the organisms. Resistance to these drugs showed a clear correlation with the production of ß-lactamase in the majority of microbial groups.

El objetivo fue evaluar la susceptibilidad a ß-lactámicos y metronidazol, y evaluar la producción de ß-lactamasas por microorganismos aislados de pacientes con periodontitis crónica y agresivo. Las muestras fueron obtenido de 50 pacientes con periodontitis y microorganismos aislados en medios de cultivo selectivos y no selectivos, identificados por métodos bioquímicos y probados a la susceptibilidad a los antimicrobianos (amoxicilina, amoxicilina/clavulanato, cefoxitina, imipenem, metronidazol, penicilina G). Los aislados fueron resistentes a por lo menos 1 mg/ml de cualquier drogas analizadas fueron evaluados para verificar la producción de ß-lactamasas por el método de doble capa (o biológico) y nitrocefina. Los resultados mostraron resistencia a amoxicilina y penicilina G, mientras la susceptibilidad a la asociación amoxicilina/ clavulanate, cefoxitina y imipenem fue ampliamente difundido entre los microrganismos. Resistencia a estas drogas mostraron una clara correlación con la producción de ß-lactamasas en la mayoría de grupos microbianos.
Susceptibilidad antimicrobiana a ß-lactámicos y metronidazol de microorganismos aislados de periodontitis crónica y agresiva
Keywords: Periodontitis; Antimicrobials; ß-lactams; Bacteria; Metronidazole; Periodontitis; Antimicrobianos; ß-lactámicos; Bacteria; Metronidazol